Hemorrhagic blood failure: Oxygen debt, coagulopathy and endothelial damage - White, Nathan J. (J Trauma Acute Care Surg, 2017)
Our understanding of the events taking place within the blood following severe injury with hemorrhagic shock is quickly evolving. Traditional concepts have given way to a detailed and nuanced understanding of coagulopathy, bleeding, and shock at the cellular and biochemical levels. In doing so, the tremendous complexity of events taking place within the blood have been illuminated and present an additional challenge. In this review, we seek to understand shock, endotheliopathy, and coagulopathy not as isolated events, but rather as the result of changes taking place within a single dynamic organ system. This review will highlight the key linkages existing between blood and endothelium and how these processes are perturbed by hemorrhagic shock to produce a syndrome that we call “hemorrhagic blood failure.” From this perspective, it may be regarded that the blood organ system fails in providing its vital functions predictably after injury. We review how accumulation of oxygen debt during shock leads to endotheliopathy and coagulopathy, and how current transfusion strategies may impact the syndrome of hemorrhagic blood failure.